Anamnesis: First Place in the UMCH 2016 Literary Contest - Freyre Muñoz, Rodrigo M. (2016)
First Place in the UMCH 2016 Literary Contest. There is no time or space, no names, just people and their souls that show in their actions. He could have been a Renaissance artist, a Greco-Roman philosopher, a French social revolutionary, a contemplative hermit in search of God, or a soldier in the world wars. But she, she was always her.